An Unusual Case of Choledochal Cyst - Pathak, Manish; Saxena, Rahul; Jayakumar, T.K.; Sinha, Arvind; Yadav, Taruna (European Journal of Pediatric Surgery Reports, 2018)
Choledochal cyst (CC) is an important surgical cause of jaundice in infants. Infantile variant of CC can mimic biliary atresia in clinical presentation. CC associated with biliary atresia is well described in literature. We encountered an atretic variant of CC that has not been described in literature ever. The characteristics of this unusual case, management, and proposed hypothesis to its pathogenesis are discussed here.
Keywords: choledochal cyst; cystic biliary atresia; atretic variant